Modulation of Presynaptic Ca(2+) Entry by AMPA Receptors at Individual GABAergic Synapses in the Cerebellum - Rusakov, Dmitri A. (Society for Neuroscience, 2005)
Cerebellar Purkinje cells (PCs) receive GABAergic input that undergoes powerful retrograde modulation by presynaptic cannabinoid and glutamate receptors. Here we examine a distinct modulatory mechanism at these synapses, which does not require postsynaptic depolarization and acts via presynaptic AMPA receptors. We find that this mechanism operates mainly in the somatic vicinity of PCs in which large boutons of basket cell axons form synapses on the PC soma. We use fast confocal microscopy and detailed kinetic modeling to estimate that, in these boutons, an action potential opens 100-200 Ca(2+) channels, eliciting a brief 3-5 μm transient, followed by a longer-term, 15-30 nm rise of free Ca(2+) (above the resting level of ∼100 nm). Brief activation of local AMPA receptors suppresses Ca(2+) entry (probably by silencing 20-40 P/Q-type channels) in a subgroup of terminals that tend to show a higher dynamic range of Ca(2+) signaling. The results provide the first quantitative description of presynaptic Ca(2+) kinetics and its modulation by AMPA receptor activation (most likely via a glutamate spillover-mediated mechanism) at identified GABAergic synapses.